Survey of Cytoscopy Performance at the Time of Hysterectomy [10]. (May 2015) - Vaynberg, Dina; Goldberg, Jay; Jaspan, David; White, Chase Michael
Abstract : OBJECTIVE: To determine third-year and fourth-year obstetrics and gynecology residents' current experience with and opinion toward cystoscopy at the time of hysterectomy. METHODS: A nine-part questionnaire was designed to assess the utilization of cystoscopy at the time of hysterectomy. Respondents were queried regarding their familiarity with literature regarding selective compared with universal cystoscopy, the number of cystoscopies they have done, how often cystoscopy has been performed for the specific types of hysterectomy they have participated in, and their plans regarding the performance of selective compared with universal cystoscopy for specific types of hysterectomy after they complete their training. The online survey, created onwww.surveymonkey.com, was sent to third-year and fourth-year obstetrics and gynecology residents in accredited U.S. programs. RESULTS: Fifty-six third-year and fourth-year obstetrics and gynecology residents completed the survey. Fifty-nine percent reported familiarity with literature regarding selective compared with universal cystoscopy. Seventy-nine percent had been involved with a hysterectomy having a bladder or ureter injury. The average number of cystoscopies performed was 44. Residents reported that cystoscopy was performed in more than 90% of the following types of hysterectomy: vaginal hysterectomy (VH) 12%, laparoscopically assisted vaginal hysterectomy (LAVH) 14%, supracervical hysterectomy (SCH) 0%, total abdominal hysterectomy (TAH) 2%, laparoscopically assisted supracervical hysterectomy (LASH) 7%, total laparoscopic hysterectomy (TLH) 29%, and those including removal of adnexa 5%. Postresidency, universal cystoscopy was planned during 34% of VHs, 34% of LAVHs, 13% of SCHs, 16% of TAHs, 21% of LASHs, 48% of TLHs, and 14% of hysterectomies with removal of adnexa. CONCLUSION: Universal cystoscopy was performed in the minority for all types of hysterectomy. Residents plan to perform universal cystoscopy more frequently than occurred in their training.